Intravenous vitamin C monotherapy in critically ill patients: a systematic review and meta-analysis of randomized controlled trials with trial sequential analysis. - Lee, Zheng-Yii; Ortiz-Reyes, Luis; Lew, Charles Chin Han; Hasan, M. Shahnaz; Ke, Lu; Patel, Jayshil J.; Stoppe, Christian; Heyland, Daren K. (Annals of Intensive Care, 2023)
Background: A recent landmark randomized controlled trial (RCT) in septic patients demonstrated an increased risk of death and persistent organ dysfunction with intravenous Vitamin C (IVVC) monotherapy, which represents a disparate result from previous systematic reviews and meta-analyses (SRMA). We performed an updated SRMA of IVVC monotherapy to summarize and explore heterogeneity across current trials and conduct trial sequential analysis (TSA) to guard against type-I or type-II statistical errors. Methods: RCTs evaluating IVVC in adult critically ill patients were included. Four databases were searched from inception to 22 June 2022 without language restrictions. The primary outcome was overall mortality. Random effect meta-analysis was performed to estimate the pooled risk ratio. TSA for mortality was performed using the DerSimonian–Laird random effect model, alpha 5%, beta 10%, and relative risk reduction (RRR) of 30%, 25%, and 20%. Results: We included 16 RCTs (n = 2130). IVVC monotherapy is associated with significant reduction in overall mortality [risk ratio (RR) 0.73, 95% confidence interval (CI) 0.60–0.89; p = 0.002; I2 = 42%]. This finding is supported by TSA using RRR of 30% and 25%, and sensitivity analysis using fixed-effect meta-analysis. However, the certainty of our mortality finding was rated low using GRADE due to the serious risk of bias and inconsistency. In a priori subgroup analyses, we found no differences between single vs multicenter, higher (≥ 10,000 mg/day) vs lower dose and sepsis vs non-sepsis trials. Post-hoc, we found no differences in subgroup analysis of earlier (< 24 h) vs delayed treatment, longer (> 4 days) vs shorter treatment duration, and low vs other risk of bias studies. IVVC may have the greatest benefit in trials that enrolled patients above (i.e., > 37.5%; RR 0.65, 95% CI 0.54–0.79) vs below (i.e., ≤ 37.5%; RR 0.89, 95% CI 0.68–1.16) median control group mortality (test for subgroup differences: p = 0.06), and TSA supported this. Conclusions: IVVC monotherapy may be associated with mortality benefits in critically ill patients, particularly in patients with a high risk of dying. Given the low certainty of evidence, this potentially life-saving therapy warrants further studies to identify the optimal timing, dosage, treatment duration, and patient population that will benefit most from IVVC monotherapy. PROSPERO Registration ID: CRD42022323880. Registered 7th May 2022.